2013
DOI: 10.1186/1756-3305-6-135
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic stellate cells increase in Toxoplasma gondii infection in mice

Abstract: BackgroundToxoplasma gondii is a ubiquitous protozoan parasite that can infect humans and animals. The severity of toxoplasmosis varies according to the immune status of the individual, parasite strain, and host species. In mammalian species, it has been observed that severe lesions of acute toxoplasmosis form in visceral organs such as the liver, lung, and spleen. Some epidemiological studies have reported an association of T. gondii infection with liver cirrhosis.MethodsAcute infection was induced in fifteen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 21 publications
6
23
0
2
Order By: Relevance
“…Toxoplasmosis causes severe and progressive damage to the liver (8,9,40), resulting in alterations in liver metabolism (40). We found that plasma AST and ALT activities were increased in T. gondii-infected gerbils, consistent with previous studies conducted on rats (14,41).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Toxoplasmosis causes severe and progressive damage to the liver (8,9,40), resulting in alterations in liver metabolism (40). We found that plasma AST and ALT activities were increased in T. gondii-infected gerbils, consistent with previous studies conducted on rats (14,41).…”
Section: Discussionsupporting
confidence: 90%
“…Toxoplasma gondii is an obligate intracellular parasite that frequently infects warm-blooded animals, including humans (9,11,18). Toxoplasma gondii is one of the most common parasites throughout the world (18) which can cause either acute or chronic infection (36).…”
Section: Introductionmentioning
confidence: 99%
“…Because development and clinical course of these comorbidities are often associated with an increased production of various pro-and antiinflammatory cytokines which are overlapping with T H 1 and T H 2 type of cytokines generated by T.gondii infection, such an excess of various factors and released biomediators may exert beneficial or harmful effects in the host, depending on their final constellations in the body. These suggestions are in agreement with recent reports that emphasized an important role of the parasite in development of liver damage and T. gondii-related hepatitis [39][40][41] .…”
Section: Group Of Animalssupporting
confidence: 93%
“…1E). When individual tissues were dissected and weighed, we found that inguinal subcutaneous white adipose tissue (scWAT), epigonadal visceral white adipose tissue (vWAT) and quadricep muscle mass (Quad) were significantly reduced at two-weeks post infection and hepatomegaly was also observed, consistent with published reports of acute T. gondii infection in the liver (Atmaca et al, 2013). (Fig.…”
Section: T Gondii Infection Leads To Sustained Cachexia In Micesupporting
confidence: 88%